1997
DOI: 10.1002/clc.4960200104
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical markers of coagulation activation in mitral stenosis, atrial fibrillation, and cardiomyopathy

Abstract: Summary: Advances in the understanding of the biochemistry of the mechanism ofhemostasis have led to the development of sensitive methods for determining levels of markers which reflect thrombin activity (thrombin-antithrombin I11 complex, fibrinopeptide A, FI +2 fragment), active fibrinolysis (D-dimer, plasmin-a2-plasmin inhibitor complex), and platelet activity (platelet factor 4, P-thromboglobulin) in vivo. Measurement of these markers may be useful in identifying patients with various cardiovascular disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…In addition, it is associated with an elevated incidence of thrombus in the left atrium (16% vs. 1%) compared to patients without any cardiac arrhythmias [8,53]. As opposed to healthy individuals, patients suffering from rheumatic cardiac disease and AF have been shown to have higher ADP-induced platelet aggregation levels, higher concentrations of beta-thromboglobulins and PF4, signifying platelet activation, and glycocalicin (GPIb fragment) as a marker of damage to the thrombocytic membrane [25].…”
Section: Role Of Platelets In the Pathogenesis Of Thromboembolic Compmentioning
confidence: 99%
“…In addition, it is associated with an elevated incidence of thrombus in the left atrium (16% vs. 1%) compared to patients without any cardiac arrhythmias [8,53]. As opposed to healthy individuals, patients suffering from rheumatic cardiac disease and AF have been shown to have higher ADP-induced platelet aggregation levels, higher concentrations of beta-thromboglobulins and PF4, signifying platelet activation, and glycocalicin (GPIb fragment) as a marker of damage to the thrombocytic membrane [25].…”
Section: Role Of Platelets In the Pathogenesis Of Thromboembolic Compmentioning
confidence: 99%
“…These investigators concluded that thrombin activity, but not platelet activity, is increased in patients with heart failure and may be linked to left ventricular enlargement and dysfunction [11]. These authors also found that patients with AF but normal systolic function had a pattern similar to that seen in CHF, suggesting mechanic similarities between these conditions [12].…”
Section: Dilated Cardiomyopathy and Chronic Congestive Heart Failurementioning
confidence: 92%
“…Its half-life is about 4–5 days. Both indicators have been demonstrated as being useful markers of coagulation activation in several clinical conditions [10, 11, 12, 13, 14, 15, 16]. AF is associated with uncoordinated atrial contractility and results in abnormalities of intracardiac flow and a subsequent prothrombotic state.…”
Section: Discussionmentioning
confidence: 99%